Unsteady Aerodynamic and Dynamic Analysis of the Meridian UAS in a Rolling-Yawing Motion - Lykins, Ryan (University of Kansas, 2014)
The nonlinear and unsteady aerodynamic effects of operating the Meridian unmanned aerial system (UAS) in crosswinds and at high angular rates is investigated in this work. The Meridian UAS is a large autonomous aircraft, with a V-tail configuration, operated in Polar Regions for the purpose of remotely measuring ice sheet thickness. The inherent nonlinear coupling produced by the V-tail, along with the strong atmospheric disturbances, has made classical model identification methods inadequate for proper model development. As such, a powerful tool known as Fuzzy Logic Modeling (FLM) was implemented to generate time-dependent, nonlinear, and unsteady aerodynamic models using flight test data collected in Greenland in 2011. Prior to performing FLM, compatibility analysis is performed on the data, for the purpose of systematic bias removal and airflow angle estimation. As one of the advantages of FLM is the ability to model unsteady aerodynamics, the reduced frequency for both longitudinal and lateral-directional motions is determined from the unbiased data, using Theodorsen's theory of unsteadiness, which serves as an input parameter in modeling. These models have been used in this work to identify pilot induced oscillations, unsteady coupling motions, unsteady motion due to the slipstream and cross wind interaction, and destabilizing motions and orientations. This work also assesses the accuracy of preliminary aircraft dynamic models developed using engineering level software, and addresses the autopilot Extended Kalman Filter state estimations.